The utility of Blogs as a Tool for Online Services of Small Libraries (LIS TODAY, 2022)
The way and circumstances have changed in the COVID-19 era. It is why effective and reliable online  library services has become essential for every library, but providing online services especially for small  libraries is relatively difficult and blogs have emerged as an effective tool for online services by small libraries. The present paper explores the concept, types of blogs, some of the major open source blogging tools and its  utility in library services
Keywords: Blogs; Weblog; Blogging; Blogger; Microblog; Wordpress